A longitudinal ecological study of seasonal influenza deaths in relation to climate conditions in the United States from 1999 through 2011. Issue 1 (1st January 2018) - Geier, David A.; Kern, Janet K.; Geier, Mark R.
ABSTRACT: Introduction: Influenza is an acute respiratory disease with significant annual global morbidity/mortality. Influenza transmission occurs in distinct seasonal patterns suggesting an importance of climate conditions on disease pathogenesis. This hypothesis-testing study evaluated microenvironment conditions within different demographic/geographical groups on seasonal influenza deaths in the United States. Materials and methods: The United States Centers for Disease Control and Prevention (CDC) Wonder online computer interface was utilized to integrate and analyze potential correlations in data generated from 1999 through 2011 for climate conditions of mean daily sunlight (KJ/m 2 ), mean daily maximum air temperature ( o C), mean daily minimum air temperature ( o C), and mean daily precipitation (mm) from the North America Land Data Assimilation System (NLDAS) database and on influenza mortality (ICD-10 codes:J09, J10, or J11) from the Underlying Cause of Death database. Results and discussion: Significant inverse correlations between the climate conditions of temperature, sunlight, and precipitation and seasonal influenza death rate were observed. Similar effects were observed among males and females, but when the data were separated by race and urbanization status significant differences were observed. Conclusion: This study highlights key factors that can help shape public health policy to deal with seasonal influenza in the United States and beyond.